Varietal integrity, damage abatement, and productivity: Evidence from the cultivation of Bt cotton in Pakistan - Ma, Xingliang; Smale, Melinda; Spielman, David J.; Zambrano, Patricia; Nazli, Hina; Zaidi, Fatima (International Food Policy Research Institute, 2016)
Bt cotton remains one of the most widely grown biotech crops among smallholder farmers. Numerous studies, including those previously conducted in Pakistan, attest to its yield and cost advantages. However, the effectiveness of Bt toxin, which depends on many technical constraints, is heterogeneous. Furthermore, in Pakistan, the diffusion of Bt cotton varieties occurred despite a weak regulatory system and without seed quality control; evidence demonstrates that varieties sold as Bt may not contain the genes or express them effectively. We use data collected from a sample that is statistically representative of the nation’s cotton growers to test the effects of Bt cotton use on productivity in a damage control framework. Unlike previous studies, we employ five measures of Bt identity: name, official approval status, farmer belief, laboratory tests of Bt presence in plant tissue, and biophysical assays measuring Bt effectiveness. Only farmers’ belief that a variety is Bt affects cotton productivity. Although all measures reduce damage from pests, the biophysical indicators have the largest effect, and official approval has the weakest. For applied economists, findings highlight the importance of getting the data right concerning Bt. For policy makers, they suggest the need, on ethical if not productivity grounds, to monitor variety integrity closer to point of sale.